The Development of Cooperative Problem Solving Oriented Teaching Materials to Improve Student Learning Outcomes - Arie Arma Arsyad; Nurfitra Yanto; St. Mutia Alfiyanti Muhiddin (EduLine: Journal of Education and Learning Innovation, 2023)
This studied aims to produce practical and effective cooperative problem solving oriented teaching materials to improve student learning outcomes in optical material. This research was carried out in three stages, namely defining, designing, and developing teaching materials by implementing 4 teaching materials for 18 class VIII students of SMP Negeri 3 Makassar in the fourth semester of the 2014/2015 school year used the one group pretest posttest design and the results research was analyzed with descriptive analysis techniques. The research data obtained: the validator's assessment of lesson plans, Student Books, LKPD, and assessment sheets with valid categories. Assessment of Student Books and LKS also had a very high level of legibility. The implementation of lesson plans with a score of 3,99 was categorized as well implemented. N-gain student knowledge learning outcomes increased 0,63 and student learning outcomes problem solving skills increased 0,72. Students gave a positive response to the learning activities of the CPS model. The results of the research show that learning tools with the CPS model are valid, practical, and effective for improving student learning outcomes.